Reduction of Cross-Polarization in a Single Offset Parabolic Reflector - Cuevas Castillo, Jesus Gustavo; Tienda Herrero, Carolina; Encinar, Jose Antonio; Krieger, Gerhard (European Conference on Antennas and Propagation (EuCAP), 2015)
reflectarray, bifocal
DLR Import::2019-04-03